Optimalisasi Caracter Building Berbasis Kurikulum 2013 Dalam Kegiatan Ekstrakurikuler Pramuka Kecamatan Pagelaran Kabupaten Malang - Dwi Agus Setiawan (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2018)
The purpose of this devotion is to optimize character building for students and teachers in SDN Karanguko 02 Kec Pagelaran kab. Poor. The benefit of this dedication is to improve the character of the elementary school according to the practice of practice in the extracurricular activities of the Boy Scouts, increasing the ability of partners to overcome the problems in handling the moral decline and social attitude of children in school and community. Increase partner knowledge that through extracurricular activities scout familiarize children in good behavior and good character. The methods undertaken in this program of devotion are through field visits and socialization, rigging training in scouts, morse password skills training, and mentoring activities and research reports konslutasi. The result of the program has shown that the partner has good response, active in the discussion and questioning, the partner is able to analyze the learning problem. The research result shows: first the training material in scouting activity containing character values, such as those in SDN Karangsuko 02 the material prioritizes to form the character of discipline and responsible.